The ethnosemiotic method for the study of consumer practices - Boero, Marianna (E|C, 2020)
This paper examines the relationship between the semiotic method and the ethnographic one for the study of consumption practices. After having theoretically framed the object of investigation and recalled some foundational works on the subject, the different methods for the analysis of consumption practices will be described, highlighting their strengths and weaknesses. Particular space will be reserved to the discussion of the ethnosemiotic perspective, which aims to understand what value of meaning it is possible to attribute to the practices as objects of a scientific investigation.